Clinical and Echocardiographic Assessment of Patients with Dilated Cardiomyopathy - Aryal, Madhu (Journal of Nepalgunj Medical College, 2022)
Introduction: Cardiomyopathy is the disorder of the heart muscles which can be dilated, hypertrophic or restrictive type. Dilated cardiomyopathy is caused by genetic and non-genetic causes but many of the causes are still not known. Echocardiography is an important imaging technique to diagnose and manage dilated cardiomyopathy.Aims: This study aims to assess the clinical and echocardiographic findings among patients with dilated cardiomyopathy.Methods: This is a cross-sectional, observational study conducted in Nepalgunj Medical College from January 2021 to June 2021. A total of 61 patients with dilated Cardiomyopathy were enrolled after obtaining written informed consent. Clinical examination and echocardiographic findings were recorded and data analysis was done using Statistical Package for Social Sciences.Results: The participants included 31 men and 30 women with dilated cardiomyopathy. The mean age of the participants was 58.49 + 15.46 years. The most common complaint was shortness of breath 84.5% and the most common clinical presentation was bilateral basal crepitation 98.4%. The patients mostly had diastolic left ventricle internal diameter of 5.5-6 cm and ejection fraction of 21-30%. Mitral regurgitation was observed among most 58(95.1%) of the patients.Conclusion: This study concludes that shortness of breath and bilateral basal crepitation are the most common presentation. Left ventricle dilation, reduced ejection fraction and mitral regurgitation are seen among majority of the patients.